The impact of physical activity on self-esteem in visually impaired children (19 years old) - tamar, Mohammed; azzedine, rami (sports creativity, 2025)
The upbringing of a disabled child is based on educational, psychological, social, and physical foundations, in light of the physical, psychological, social, and mental development characteristics of children. It includes modern methods in teaching the visually impaired, along with pioneering methods that focus on teaching them through developing their senses and motor skills, acquiring acceptable social behavior, increasing their knowledge, developing their mental, physical, and psychological abilities, and their linguistic repertoire through daily practice and in light of the characteristics of their mental, physical, psychological, and social development. This study aimed to determine the impact of physical activity on self-esteem among visually impaired children (aged 21-90). This was achieved through several questions focusing on individual differences in self-esteem levels (academic self-esteem and general appearance, social self-esteem and recreational self-esteem, and physical self-esteem and family self-esteem). The descriptive-analytical method was used, and the study included a sample of 91 students from the School for Blind Youth in El Achour, Algeria. Eleven students participated in these activities, while eleven did not. The results favored the students who participated in physical activities, demonstrating consistency.